2004
DOI: 10.1366/000370204322729441
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Spectroscopy as a Tool for Probing Specific Biochemical Components in Bacteria

Abstract: Treatment of bacteria with silver yields intense and highly specific surface-enhanced Raman spectroscopy (SERS) spectra from various cellular chemical components located in the vicinity of the silver colloids. In particular, we demonstrate an extreme sensitivity to flavin components associated with the cell envelope and to their state of oxidation. Different spectra, possibly associated with DNA, carboxylates, and perhaps phosphates, are obtained from the soluble interior fraction of the cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
194
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(209 citation statements)
references
References 39 publications
11
194
2
Order By: Relevance
“…It completely overcomes the shortcoming of Raman small cross sections. SERS is capable to characterize [7][8][9][10], identify [11,12], and differentiate [13,14] pathogenic microorganisms in synergy with chemometrics, based on the biochemical, chemical, and their structural properties.…”
Section: Sers Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…It completely overcomes the shortcoming of Raman small cross sections. SERS is capable to characterize [7][8][9][10], identify [11,12], and differentiate [13,14] pathogenic microorganisms in synergy with chemometrics, based on the biochemical, chemical, and their structural properties.…”
Section: Sers Effectmentioning
confidence: 99%
“…The authors used the 633 nm laser line as an excitation wavelength, therefore they were able to report the ring breathing mode band observed at 1004 cm −1 and assigned to the phenylalanine residue [10]. Excepting Knauer's group work [9,11,42] and recent studies reported by Zhou et al [12][13][14]44], when applying the in situ approach, the Leopold and Lendl SERS active substrate was not so exploited in the bacteria detection, as the usage of the 633 nm laser line is mere.…”
Section: Label-free Sers-based Assaysmentioning
confidence: 99%
“…However, the several issues inherent to the nature of the technique, mainly reproducibility, still persist and lower the applicability to its wide spread use in biological applications. The detection and identification of several biological molecules such as proteins [106][107][108][109][110], DNA [111][112][113][114], and RNA [115,116] and molecular organizations such as bacteria [117][118][119][120][121][122][123][124][125][126], yeast [127][128][129], and viruses [130,131] using SERS were reported. The detection scheme could be based on either using the intrinsic fingerprint information of the molecules or molecular structures or the use of an external label.…”
Section: Detection Identification and Characterization Of Biomacrommentioning
confidence: 99%
“…Whole microorganism detection and identification using SERS is another research area where the fingerprint spectra obtained from whole microorganisms can be used. There are a number of studies demonstrating the feasibility of technique for whole bacterial detection and identification [117][118][119][120][121][122][123][124][125][126]. The identification and classification of bacteria causing urinary tract infections were demonstrated by Goodacre group using citrate reduced AgNPs [123].…”
Section: Detection Identification and Characterization Of Biomacrommentioning
confidence: 99%
“…However, enhancement methods such as SERS will provide a solution to this problem. Several investigations into SERS of bacteria have been undertaken [21,22,23,24,25], and more recently it has been shown that SERS can reliably differentiate between different bacteria [26,27]. There is also much interest in detecting aerosols of spore-forming pathogens, with the obvious target being the identification of Bacillus anthracis.…”
Section: Spectroscopic Characterization Of Micro-organismsmentioning
confidence: 99%